On Fuzzy Statistical (O)-Convergence in Fuzzy Riesz Spaces - Abdul-Hussein Kadhim, Shatha (Al-Nahrain Journal of Science, 2020)
In this paper, we present the concepts of fuzzy order convergence, fuzzy statistical (O)-Convergence (Fso-Convergence), and fuzzy statistical Cauchy sequence in fuzzy Riesz spaces, their fundamental properties are established, some important theorems are given, and show every (Fso-Convergence) can be fuzzy statistical Cauchy and prove that any one of two sequences is fuzzy order converge leads to the second sequence is fuzzy statistical (O)-Convergence. In addition, we have also demonstrated through examples that, in general, “fuzzy ordered linear space, need not to be a fuzzy Riesz spaces”.